Cysteine cathepsins, stefins and extracellular matrix degradation during invasion of transformed human breast cell lines - Zajc, Irena (Radiology and oncology (Ljubljana), 2006)
Background. Human breast cellular model, comprising four cell lines originating from spontaneously immortalized human breast epithelial MCF10A cell line, its c-Ha-ras transfectant, MCF10AT, and two tumourigenic derivatives, cultured from two sequential mouse xenographs, MCF10AT-Ca1a and MCF10AT-Ca1d, were used to compare the relative protein concentration of cathepsins and stefins in single cells. Methods. The relative protein concentration of cathepsins and stefins in single cells was analysed by confocal microscopy, and compared to their protein expression in cell homogenates. Results. The most invasive, MCF10AT cell line contained several fold higher protein concentration of cathepsin B and increased levels of stefins, but similar levels of cathepsin L, compared with the parental MCF10A cells. This was associated with five fold higher endocytosis of Matrigel-DQ-collagen IV (DQC) and a simultaneous increase in signal overlap between DQC and cathepsin L as well as DQC and stefin B, but a decrease in that of DQC and cathepsin B overlap in the MCF10AT cells. Simultaneously, increased signal overlaps between both cathepsins and between cathepsins-stefins pairs, were observed in this cell line. Conclusions. These results suggest that the increased collagen endocytosis and degradation in theinvasive phenotype significantly affect also the subcellular localization of cysteine cathepsins and stefins. Based on these and the reports of other authors, we hypothesize that the intracellular degradation may also be assoeiated with cathepsin L, whereas cathepsin B in the ras transformed breastcells is involved in both, the intracellular and pericellular degradation of extracellular matrix during cell migration and invasion.
Keywords: breast; dojke; katepsini; novotvorbe; rak (medicina); tumor; tumorske celice; zgradba